Control de los bienes e inventarios del Gad Municipal de Echeandía - Saltos Villares, Aylis Marisela (2020)
The Municipal Decentralized Autonomous Government of the Echeandía canton, located in the province of Bolívar is the object of study with the subject CONTROL OF PROPERTY AND INVENTORIES, as an information gathering technique the interview has been used, through this process it has been possible to detect inconveniences in the warehouse department, in the same work only one person who has a post of municipal warehouse keeper, where it can be detected that not all the goods are properly coded for this reason, their physical verification cannot be made. Another serious problem is that it does not have a warehouse, for this reason, public employees who provide cleaning services to the streets of the canton, take their work tools to their respective homes, it also causes public officials to request materials or supplies for their daily tasks, their request is requested by official letter to the mayor where he sends the administrative area for due process, which is very tedious, if there were a storage place the acquisition of materials or supplies would be carried out by large quantities and their due request would be directly to their custody, in this case the warehouse keeper.